Efektivitas E-Library Of Angkasa Pura II (Elora) Dalam Meningkatkan Literasi Digital Di PT Angkasa Pura II (Persero) - Tasya Twinca Putri; Nida Handayani; Abdul Rahman; Dini Gandini Purbaningrum (International Forum of Researchers and Lecturers, 2023)
The purpose of this study is to find out how the effectiveness of the E-Library of Angkasa Pura II (Elora) in increasing digital literacy at PT Angkasa Pura II (Persero). This type of research uses qualitative methods with descriptive research types. Data collection techniques using the method of observation, interviews, and documentation. The research results were carried out from the theory of program effectiveness according to Budiani (2007:53) with 4 (four) indicators. First, namely the accuracy of the program's targets is appropriate, seen from the exact program targets, which PT Angkasa Pura II is aimed at all employees who intend to increase their knowledge. Second, the socialization of the program cannot be said to be effective as seen from the fact that there are still many employees of PT Angkasa Pura II who have not used the Elora application because the socialization does not vary only through WhatsApp groups and corporate email. Third, the program objectives are appropriate, seen from the Elora application, it really helps employees in terms of increasing digital knowledge and literacy. Fourth, program monitoring has been carried out by the organizing team through monitoring and evaluation. In addition, program monitoring can also be seen at the Management Review Meeting every month, but there is still no follow-up to make improvements as a result of the evaluation carried out.